Evaluation of the dry bean model BEANGRO V1.01 for crop production research in a tropical environment - White, Jeffrey W.; Hoogenboom, Gerrit; Jones, James W.; Boote, Kenneth J. (Cambridge University Press, 1995)
Microcomputer-based simulation models are increasingly being recommended as multipurpose tools for agricultural research. Use of a model should be conditioned by an evaluation of its performance and understanding of its limitations. This paper evaluates the responses of the process-oriented growth model for dry bean (Phaseolus vulgaris), BEANGRO V1.01, with an emphasis on the factors related to cultivar differences for production in tropical environments. Simulations of seed yield from beans grown under conditions of a known water deficit showed good agreement with observed data. The qualitative response to plant population resembled that of a field trial, and the model showed the expected linear relation between days to maturity and seed yield. Overall, the results suggest that BEANGRO has utility for certain types of agronomic studies, but that improvements are possible, particularly with respect to prediction of phenology.